Strategies to overcome physician shortages in northern Ontario: A study of policy implementation over 35 years - Pong Raymond W (BMC, 2008)
Abstract Background Shortages and maldistibution of physicians in northern Ontario, Canada, have been a long-standing issue. This study seeks to document, in a chronological manner, the introduction of programmes intended to help solve the problem by the provincial government over a 35-year period and to examine several aspects of policy implementation, using these programmes as a case study. Methods A programme analysis approach was adopted to examine each of a broad range of programmes to determine its year of introduction, strategic category, complexity, time frame, and expected outcome. A chronology of programme initiation was constructed, on the basis of which an analysis was done to examine changes in strategies used by the provincial government from 1969 to 2004. Results Many programmes were introduced during the study period, which could be grouped into nine strategic categories. The range of policy instruments used became broader in later years. But conspicuous by their absence were programmes of a directive nature. Programmes introduced in more recent years tended to be more complex and were more likely to have a longer time perspective and pay more attention to physician retention. The study also discusses the choice of policy instruments and use of multiple strategies. Conclusion The findings suggest that an examination of a policy is incomplete if implementation has not been taken into consideration. The study has revealed a process of trial-and-error experimentation and an accumulation of past experience. The study sheds light on the intricate relationships between policy, policy implementation and use of policy instruments and programmes.